Immobilization of bovine serum albumin on the chitosan/PVA film - Nurul Mujahidah Ahmad Khairuddin,; Amalina Muhammad Afifi,; Nur Awanis Hashim,; Shaza Eva Mohamad,; Katayoon Kalantari, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Chitosan/polyvinyl alcohol (Chitosan/PVA) blended film was prepared by direct blend process and solution casting methods. In order to reduce the swelling ratio and enhance the chemical and mechanical stability, Chitosan/PVA film was cross-linked with glutaraldehyde in order to produce Chitosan-g-PVA. Bovine serum albumin (BSA) was used as a model protein to incorporate into the Chitosan-g-PVA. The chemical structure and morphological characteristics of films were studied by FT-IR and scanning electron microscopy (SEM). Mechanical and physical properties of blended films such as tensile properties in the dry and wet states, water uptake and water contact angle measurement were characterized. Blending PVA and chitosan improved strength and flexibility of the films. Crosslinking with glutaraldehyde further improves the tensile strength and decrease the hydrophilicity of films. BSA immobilized on the Chitosan-g-PVA film was calculated as BSA encapsulation efficiency.